Learning to Play Music Based on Flashcards for Inculcating Character Values; Discipline, Independence and Curiosity - Dwi Kananda Tyas Sulistyo; Wadiyo Wadiyo; Restu Lanjari (Universitas Negeri Semarang, 2023)
This study discusses learning music through flashcard media to instill character values in early childhood at the Indonesian Music School (SMI) Semarang, Program Foundation of Music (FOM). There are 3 (three) main character values that will be discussed in this study. They are the value of discipline, the value of independence and the value of curiosity. The research questions of this study are the 3 (three) main character values instilled in early childhood in the Program FOM, SMI Semarang. This study uses an Inculcation Approach. This research uses descriptive qualitative method. In addition, the data collection techniques used in this study were observation, interviews and documentation. From the results of the analysis, it can be concluded that by cultivating 3 (three) main character values; discipline, independence and curiosity, students can implement them and continue to the next stage of development. So that it is in line with the purpose of character education, which is to create superior and dignified student characters.